Europejski rynek akcji i obligacji w kontekście procesów globalizacji i integracji - Żabińska, Joanna; Mizerski, Eugeniusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article analyzes results of the process of globalization and integration of the financial markets. Special attention is drawn to shares and bond markets. The article compares European and north American financial markets. The article analyzes causes of changes in economic situation on the financial market and effects of introduction of European monetary union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 383-396